Methodology for Measuring Lipid Peroxidation in Biological Materials - A Bibliography - Sri Raharjo (Indonesian Food and Nutrition Progress, 1994)
Various substances have been found and used as markers of different stages of lipid peroxidation reaction. Free radicals detection would provide more meaningful information when the method is used in clicinal studies involving living cells or tissue biopsy. Lipid oxidation products may be used as markers of lipid peroxidation, especially in food products. Each method currently available for measuring the extent of lipid peroxidation sholud be used precautiosly and its limitations shouls be anticipated.